Management of Character Education of Vocational School Students Through the Science Learning System - Deti Sulastri; Tb. Abin Syamsudin Makmun; Achmad Sanusi; Yosal Iriantara (UIN Sunan Gunung Djati Bandung, 2020)
There are still many young generations who are trapped in the global flow of immorality resulting in the erosion of character values that the education system has not been able to stop, one of which is the science learning materials. This research aims to examine and analyze character education management, specifically the character of noble morals through planning, organizing, implementing, monitoring and evaluating management, reviewed from the theory and concepts of learning management. Through the case study method with a qualitative approach, it shows that the management of student character education through the science learning system is still constrained by infrastructure resources and teacher competence. Noble moral character education in SMK by integrating religious programs based on Islamic teachings through religious literacy programs, and some SMKs have collaborated with parents of students in the context of continuous coaching, but are still limited by time in its implementation.